Hydrogeochemical characteristics of water intakes from groundwater sources in Seversk; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Karmalov A. I.; Dutova E. M. Ekaterina Matveevna; Vologdina I. V.; Pokrovsky D. S.; Pokrovsky V. D. Vitaly Dmitrievich; Kuzevanov K. K. Konstantin Konstantinovich (Hydrogeochemistry and Hydrogeoecology, 2016)
Title screen